Late Spring Freezes in Poland in Relation to Atmospheric Circulation - Ustrnul, Zbigniew; Wypych, Agnieszka; Winkler, Julie A.; Czekierda, Danuta (Quaestiones Geographicae, 2014)
Late spring freeze events, a significant agroclimatic hazard, are investigated for Poland. Daily minimum air temperatures from 184 stations for the period 1951-2010 were used to analyze the frequency and conditional probability of late spring freezes. In addition, three classification schemes were employed to investigate the atmospheric circulation responsible for late spring freezes events. The findings suggest that knowledge of the airflow influencing late spring freezes can help to understand the complex historical trends and projected future changes in freeze risk for perennial crops